Respostas
respondido por:
23
a1 = 38
a2 = 42
r = a2 - a1
r = 42 - 38 = 4 >>>>
an = a1 + ( n - 1).r
a10 =38 + 9r
a10 = 38 + 9 * 4
a10 =38 + 36 = 74 >>>>>
S10 = ( a1 + a10).10/2
S10 = ( 38 + 74 ).5
S10 = 112 * 5 = 560 >>>>> resposta
aavianna:
muito obrigado!
respondido por:
40
Encontrar a razão da PA
r = a2 - a1
r = 42 - 38
r = 4
===
Determinar o valor do termo a10
an = a1 + ( n -1 ) . r
a10 = 38 + ( 10 -1 ) . 4
a10 = 38 + 9 . 4
a10 = 38 + 36
a10 = 74
===
Soma dos 10 primeiros termos:
Sn = ( a1 + an ) . n / 2
Sn = ( 38 + 74 ) . 10 / 2
Sn = 112 . 5
Sn = 560
r = a2 - a1
r = 42 - 38
r = 4
===
Determinar o valor do termo a10
an = a1 + ( n -1 ) . r
a10 = 38 + ( 10 -1 ) . 4
a10 = 38 + 9 . 4
a10 = 38 + 36
a10 = 74
===
Soma dos 10 primeiros termos:
Sn = ( a1 + an ) . n / 2
Sn = ( 38 + 74 ) . 10 / 2
Sn = 112 . 5
Sn = 560
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás